Early experience and operative technique of robotic‐assisted partial nephrectomy. Issue 7 (12th May 2014) - Kucharczyk, John R.; Basto, Marnique; Landau, Adam; Graves, Reid; Everaerts, Wouter; Birch, Emma; Murphy, Declan; Moon, Daniel
Abstract: Background: The adoption of robotic‐assisted partial nephrectomy (RAPN) is increasing in Australia; however, to date no Australian RAPN series has been reported. This paper describes a single‐surgeon initial experience with RAPN and evaluates perioperative, pathological and oncological outcomes. Methods: Data on the first 50 consecutive patients to undergo RAPN by a single surgeon were reviewed. Demographic, perioperative, tumour characteristics and Clavien complications were collected in addition to oncological follow‐up and renal function monitoring. Results: Mean age was 58.2 ± 10.4 years, body mass index was 28.8 ± 4.5 kg/m 2 and Charlson Co‐morbidity Index was 4.6 ± 1.2. Tumour diameter was 31 ± 13 mm and RENAL score was 6.8 ± 1.5. Average total operative time was 151 ± 32.7 min, estimated blood loss was 171.1 ± 185.8 mL, warm ischaemia time was 17.8 ± 6.7 min and length of hospital stay was 3 ± 0.9 days. There were seven Clavien complications and no deaths. Estimated glomerular filtration rate did not decrease significantly post‐operatively ( P = 0.8); and there was 14.6% upstaging of chronic kidney disease scoring although no patient required dialysis. There were no positive malignant surgical margins, and to date no patient has evidence of disease recurrence. Of 50 patients, 54% had a minimum follow‐up of 6 months and 28% had a minimum follow‐up of 1 year. Conclusion: We report the largest RAPN study in Australia or New Zealand to date. Initial results suggest that RAPN can be safely introduced into the Australian public and private health systems, and has been effective in oncologic control and renal function preservation.